Human Stem Cell Transplantation: An Overview Of The Islamic Perspective's Ethical Issues In Malaysia - Muhamad Rafiqi Hehsan; Imran Mohd Pazudi; Muhammad ‘Afif Rosdin; Wan Athirah Wan Izudin; An Nisa Yustisia R; Nisya Oktia Nahdah; Zulkifli Dahalan (Penerbit USIM, 2024)
Journal of Fatwa Management and Research Volume 28 Issue 3 Page (1-20)